The Beautiful Generation : Asian Americans and the Cultural Economy of Fashion - Tu, Thuy Linh N. (Book collections on Project MUSE., 2011)
"The Beautiful Generation is a pleasure to read and a model of how cultural studies ought to be done. Thuy Linh Nguyen Tu's elegant, well-crafted account of the fashion industry demonstrates the impossibility of separating the aesthetic from the material, or the cultural from the economic. It shows how the changing roles of culture in the global economy can be luminously traced through a focused, interdisciplinary methodology."--Kandice Chuh, Author of Imagine Otherwise: On Asian Americanist Critique --Book Jacket.